"That Indefinite Area of Toleration": Criminal Conspiracy and Trade Unions in Ontario, 1837-77 - Tucker, Eric (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1991)
Abstract During the first three quarters of the nineteenth century, the question of whether trade unions in Ontario were criminal conspiracies under common law was never clearly determined. By examining the development and interaction of the legal and social zones of toleration we can illuminate how law was shaped by and shaped early struggles between workers and employers. The statutory reforms of 1872 clearly defined a narrow zone of legal toleration in which trade unions were accepted as labour market organizations while the means they could to pursue their objectives were restricted. The contours of industrial legality which began to emerge during this period remain a salient feature of current labour law.